The Implementation of Weighted Products in the Support System of Scholarship Acceptance Decisions at the MA AL-Falahiyah AL-Asytari - Ri Sabti Septarini; Rohmat Taufiq; Saiman Al Fattah (Teknik Informatika Universitas Pamulang, 2020)
Scholarships are a form of appreciation given to individuals in order to continue their education to a higher level. The scholarship program held to ease the burden on students in pursuing a period of study. Especially in matters of cost. MA Al-Falahiyah Al-Asytari organizes a scholarship program for students based on criteria determined by the school. The need for a scholarship naming decision system is one of the core needs so that the selection of scholarship acceptance is more objective and practical. Development of a Decision Support System (DSS) using the Weighted Product model chosen because it was able to select the best alternatives from several alternatives and their advantages in weighting techniques. In designing the system using Unified Modeling Language (UML) and making applications using PHP and MySQL as a database. From the research the authors have described, it concluded that the weight product method could use as one method in developing a decision support system for scholarship recipients at the MA Al-Falahiyah Al-Asytari, by inputting data from students who submit scholarships to calculating grades based on criteria which specified.